Individual differences in impulsive and risky choice: effects of environmental rearing conditions - Kirkpatrick, Kimberly; Marshall, Andrew T.; Smith, Aaron P.; Koci, Juraj; Park, Yoonseong (My University, 2014)
The present experiment investigated early-rearing environment modulation of individual differences in impulsive and risky choice. Rats were reared in an isolated condition (IC; n = 12), in which they lived alone without novel stimuli, or an enriched condition (EC; n = 12), in which they lived among conspecifics with novel stimuli. The impulsive choice task involved choices between smaller-sooner (SS) versus larger-later (LL) rewards. The risky choice task involved choices between certain-smaller (C-S) versus uncertain-larger (U-L) rewards. Following choice testing, incentive motivation to work for food was measured using a progressive ratio task and correlated with choice behavior. HPLC analyses were conducted to determine how monoamine concentrations within the prefrontal cortex (PFC) and nucleus accumbens (NAC) related to behavior in different tasks. IC rats were more impulsive than EC rats, but they did not differ in risky choice behavior. However, choice behavior across tasks was significantly correlated (i.e., the more impulsive rats were also riskier). There were no group differences in monoamine levels, but noradrenergic and serotonergic concentrations were significantly correlated with impulsive and risky choice. Furthermore, serotonin and norepinephrine concentrations in the NAC significantly correlated with incentive motivation and the timing of the reward delays within the choice tasks. These results suggest a role for domain general processes in impulsive and risky choice and indicate the importance of the NAC and/or PFC in timing, reward processing, and choice behavior.
Keywords: Impulsive choice; Risky choice; Differential rearing; Individual difference; Monoamine concentration; Rat